2023
DOI: 10.1002/cbdv.202201048
|View full text |Cite
|
Sign up to set email alerts
|

New Isopropyl Chromone and Flavanone Glucoside Compounds from the Leaves of Syzygium cerasiforme (Blume) Merr. & L.M.Perry and Their Inhibition of Nitric Oxide Production

Abstract: A new isopropyl chromone (1) and a new flavanone glucoside (2) together with eleven known compounds (3 -13) were isolated from the leaves of Syzygium cerasiforme (Blume) Merr. & L.M.Perry. Their structures were elucidated as 5,7-dihydroxy-2-isopropyl-6,8-dimethyl-4H-chromen-4-one (1), 5,7-dihydroxyflavanone 7-O-β-D-(6''-O-galloylglucopyranoside) (2), strobopinin (3), demethoxymatteucinol (4), pinocembrin-7-O-β-D-glucopyranoside ( 5), (2S)-hydroxynaringenin-7-O-β-D-glucopyranoside (6), afzelin (7), quercetin (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The anti-inflammatory activity of this new chromone was evaluated, and it was concluded that it inhibits NO production in LPS-activated RAW264.7 cells with an IC 50 value of 12.28 ± 1.15 μM, compared to a positive control, N Gmonomethyl-L-arginine acetate, which presents an IC 50 value of 32.50 ± 1.00 μM. 35 Abronia nana (Nyctaginaceae) is an ornamental plant that inhabits the desert area of North America whose pharmacological potential is not yet well-established. Following on from previous studies, carried out to find antisepsis lead compounds from natural sources, Lee and colleagues isolated a new Cmethylcoumarinochromone from Abronia nana suspension cultures.…”
Section: Aquilaria Sinensismentioning
confidence: 99%
See 3 more Smart Citations
“…The anti-inflammatory activity of this new chromone was evaluated, and it was concluded that it inhibits NO production in LPS-activated RAW264.7 cells with an IC 50 value of 12.28 ± 1.15 μM, compared to a positive control, N Gmonomethyl-L-arginine acetate, which presents an IC 50 value of 32.50 ± 1.00 μM. 35 Abronia nana (Nyctaginaceae) is an ornamental plant that inhabits the desert area of North America whose pharmacological potential is not yet well-established. Following on from previous studies, carried out to find antisepsis lead compounds from natural sources, Lee and colleagues isolated a new Cmethylcoumarinochromone from Abronia nana suspension cultures.…”
Section: Aquilaria Sinensismentioning
confidence: 99%
“…and L.M. Perry, a plant used in Vietnam in folk medicine . Its structure was elucidated as 5,7-dihydroxy-2-isopropyl-6,8-dimethyl-4 H -chromen-4-one ( 48 , Figure ) by the analysis of HR-ESI-MS, NMR, and ECD spectral data.…”
Section: Chromones and Chromanones From Natural Sourcesmentioning
confidence: 99%
See 2 more Smart Citations